2010
DOI: 10.1007/s00542-010-1070-4
|View full text |Cite
|
Sign up to set email alerts
|

Axial and shear fracture strength evaluation of silicon microneedles

Abstract: This research aims to quantify fracture limits of hollow silicon microneedles due to axial and shear forces, and validate their use on human skin. Needle failure due to axial and shear loads may be due to heterogeneous peak stresses within the bulk material. Analytical determination of physical usage limits of microneedles can be misleading, as beam fracture models do not translate well to the micro-scale. In this research, various sizes of hollow silicon microneedles were fabricated. Their point of failure du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…The fracture of microneedles occurred at 0.85 ± 0.15 N, in most cases at the predicted position as obtained by FEA analyses, which is in good agreement with the calculated values. Khanna et al [43] determined critical shear forces of 0.36 N and 2.75 N for 36 and 33 gauge hollow microneedles, respectively, which is close to our measured values, regardless of the different designs used by Khanna. By taking into account the maximal range of applied forces during experimental work (1-10 N for 10 × 10 array) and measured lateral fracture forces (0.85 ± 0.15 N), the safety margin was determined. The worst case safety margin in our case is given as a ratio between the lowest measured microneedle shear fracture force (0.7 N) and the maximal axial force applied onto the microneedle during penetration (100 mN), which gives a value of 7.…”
Section: Evaluation Of Silicon Mna Safety Marginsupporting
confidence: 89%
See 1 more Smart Citation
“…The fracture of microneedles occurred at 0.85 ± 0.15 N, in most cases at the predicted position as obtained by FEA analyses, which is in good agreement with the calculated values. Khanna et al [43] determined critical shear forces of 0.36 N and 2.75 N for 36 and 33 gauge hollow microneedles, respectively, which is close to our measured values, regardless of the different designs used by Khanna. By taking into account the maximal range of applied forces during experimental work (1-10 N for 10 × 10 array) and measured lateral fracture forces (0.85 ± 0.15 N), the safety margin was determined. The worst case safety margin in our case is given as a ratio between the lowest measured microneedle shear fracture force (0.7 N) and the maximal axial force applied onto the microneedle during penetration (100 mN), which gives a value of 7.…”
Section: Evaluation Of Silicon Mna Safety Marginsupporting
confidence: 89%
“…According to Khanna et al [43] a Si microneedle failure can be generally attributed to lateral (shear) forces, since the usage of microneedles involves stresses due to non-uniformity of skin contour and human movements, both which result in lateral forces acting onto, and consequently leading to the breakage of, the microneedles. In practice we found that force application along directions other than normal onto the skin may easily occur.…”
Section: Evaluation Of Silicon Mna Safety Marginmentioning
confidence: 99%
“…This has allowed a wealth of MN sizes and shapes to be manufactured, which has already been discussed as having an influence on MN insertion. Silicon MNs have significant strength mechanically, and this allows silicon MNs to sufficiently insert into skin [ 151 , 152 ]. Deformation and stress testing of silicon MNs of concave conic shape were undertaken to predict the incidence of MN deformation [ 153 ].…”
Section: Parameters Affecting Mn Insertionmentioning
confidence: 99%
“…The first modalities developed were solid and hollow MNs, fabricated from silicon, metals and glass. [28][29][30][31][32] In particular, hollow MNs have been tested previously in the delivery of biologics. Harvey et al (2011) used a delivery device consisting of three 1 mm 34G steel needles incorporated into a fluid-disrupting hub to deliver etanercept (132 kDa) intradermally.…”
Section: Discussionmentioning
confidence: 99%